The Effectiveness of Role Playing Games-Based Learning in Teaching History - Mutoharoh, Rina; Anfasya, Muhammad Ikhsan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to produce a product and explain the effectiveness of role-playing game-based learning media to explain historical events (the General Offensive of March 1) for high school students or their equivalents. The research uses the Research and Development (R&D) method, which, according to Prof. Sugiyono, consists of 10 stages up to mass production. In practice, the RPG game for the historical event of the General Offensive of March 1 only reached the product trial stage. In the effectiveness testing process, the sample was obtained from students of MAN 1 Surakarta. The results of the material expert validation produced an average score of 93.0%, proving that the learning media is effective for teaching the history of the General Offensive of March 1. Role-playing game-based learning media can be an effective and enjoyable way to utilize technology in education, especially in explaining historical material.